Multimethod Research, Causal Mechanisms, and Case Studies : An Integrated Approach - Goertz, Gary (New Jersey Princeton University Press, 2017)
An innovative and accessible textbook on multimethod and case-study research. Multimethod research has become indispensable to doing social science, and is essential to anyone who conducts large-scale research projects in political science, sociology, education, comparative law, or business
Include References and Index
Keywords: Mixed Methods Research -- Social Sciences Research Methodology -- Causation Research